Nutraceuticals: -In Skin Care and Formulations A Review - Swapna Saubhagya Nayak,; Balu t. Jagtap, (Asian Journal of Pharmaceutical Research and Development, 2025)
The physiologically active ingredients that sustain health advantages are known as nutraceutical. Due to their therapeutic benefits, these products are crucial to human health care. The nutritional advantages, medicinal effects, and safety profile of nutraceuticals have earned them prominence. Nutraceuticals are well known throughout the world and are expanding in the sphere of services like illness prevention and health care promotion. For a better knowledge of nutraceuticals, this review has also provided instances and explanations of numerous drug nutraceutical interactions. Numerous nutraceutical patents have been filed in a variety of agricultural and medical fields. In addition to being used for nutrition, nutraceuticals have been used as a support therapy for the prevention and treatment of a number of illnesses, including to lessen the negative effects of chemotherapy for cancer. Micronized food items and other nutraceutical supplements with enhanced health advantages are also produced thanks to nanotechnology. There has also been discussion of the most recent important discoveries (clinical research) on nutraceuticals that demonstrate the therapeutic effect of the bioactive compounds in these products on a range of illnesses. Numerous internal and environmental factors, including hormone imbalances, UV radiation, and the biological evolution of cells, all contribute to the ongoing aging of the skin. These internal and external factors increase the appearance of aging skin, which is characterized by telangiectasias, wrinkles, roughness, loss of elasticity, and diminished firmness. Nutraceuticals have been researched all year long to combat and postpone a number of food-related issues.